2020
DOI: 10.14260/jemds/2020/100
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein in Metabolic Healthy Obesity (MHO)

Abstract: BACKGROUND Metabolically Healthy Obesity/Metabolic Healthy Obesity (MHO) is a paradox in scientific medical literature and discussion is still on regarding the safety status of MHO phenotype. It is an obesity phenotype where the subjects have BMI more than or equal to 30 Kg/m 2 but are devoid of conventional metabolic complications such deranged lipid profile, altered glucose tolerance, or metabolic syndrome as they have less adverse inflammatory profile, low visceral fat, less disturbed insulin signalling, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…C-reactive protein (CRP) is an acute-phase protein that is increased in infections, inflammatory conditions, and even cancers [7][8]. High sensitivity CRP (hsCRP) is a highly sensitive form of CRP.…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein (CRP) is an acute-phase protein that is increased in infections, inflammatory conditions, and even cancers [7][8]. High sensitivity CRP (hsCRP) is a highly sensitive form of CRP.…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed the case studies, research articles and protocols to collect information on study drugs [13][14][15]. Various research studies on obesity were reported increasing prevalence and associated risk with obesity [16][17][18]. Studies on assessments of obesity and lipid profiles in different conditions were reviewed [19][20][21].…”
Section: Plan To Promote Participants Retention and Complete Follow Upmentioning
confidence: 99%
“…Ashoka by virtue of its Ttikta, Kashaya, Laghu, Ruksha, GunaKaphaghna in nature [17]. Related studies on obesity and assessment were reviewed [18][19][20]. This Dravya displays Karma like Lekhana, Rookshana, and Karshana.…”
Section: Probable Mode Of Action Of Vastimentioning
confidence: 99%